Direct and indirect associations of cognitive reappraisal and suppression with disease biomarkers. Issue 3 (4th March 2019) - Ellis, Erin M.; Prather, Aric A.; Grenen, Emily G.; Ferrer, Rebecca A.
Abstract: Objective: Habitual use of emotion regulation strategies may influence physical health. We examined whether the tendencies to employ cognitive reappraisal and suppression were associated with health biomarkers, and whether stress and sleep quality mediated these associations.Design & main outcome measures: Using data from the Biomarkers substudy ( n  = 1255) of the national Midlife in the U.S. Study, we tested the hypothesis that there would be indirect, but not direct, associations of cognitive reappraisal and suppression to biomarker indicators of multisystem physiological dysregulation, that is, allostatic load (AL). We computed the proportion of biomarkers in the highest risk quartile within seven biological systems, and summed these scores to compute AL. Associations with the biological systems were also examined separately.Results: Neither reappraisal nor suppression was directly associated with AL or biomarker function in the seven biological systems. Suppression was indirectly associated with higher AL and greater dysregulation in the inflammatory, metabolic, and hypothalamic-pituitary-adrenal systems via its relations to stress and sleep, p  < 0.05. Reappraisal was indirectly associated with lower AL and less metabolic and inflammatory dysregulation, p s<0.05.Conclusions : Suppression and reappraisal may have different downstream health effects via stress, sleep, and biomarker expression, suggesting malleable emotion regulation strategies may be an important intervention target.